PENGARUH KUALITAS PRODUK, PROMOSI DAN DESAIN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA LISTRIK DI DEALER MEGA SINAR BINTANG BESUKI SITUBONDO - Ediyanto, Ediyanto (Relawan Jurnal Indonesia, 2023)
This study aims to find out the product quality, promotion and design variables partially influence the purchase decision variable, to find out the product quality, promotion and design variables simultaneously influence the purchase decision variable, to find out among the product quality variables, promotion and design have a dominant influence on the purchase decision variable. The method used is quantitative. The results of the study are the equation of multiple linear regression Y = 2,238E-16 + 0,043 X1 + 0,542 X2 + 0,230 X3 + e. partially the quality of the product has no significant effect with a t-value greater than t table (0,429) < (1,993) or sig α 0,669 > 0,05, promotion has a significant positive effect with a t-value greater than t table (5,865) > (1,993) or sig α 0,000 < 0,05, the design has a significant positive effect with a tcount greater than t table (2,284) > (1,993) or sig α 0,025 < 0,05. Simultaneously the product quality, promotion, and design influence on purchasing decisions with a calculated F value of 19,083 values ​​greater than F table that is 2,73 or F calculated 19,083 > F table 2,73. The most influential dominant variable in this study is promotion with a value of 5,865